Activity Test of Catalase Enzyme in Rhizospheric Soil Bacteria - Susanti, Berliana Putri; Yuliani, Apreza Eka; Hidayatullah, Ahmad Fauzan; Sutrisno, Sutrisno (Bioeksperimen: Jurnal Penelitian Biologi, 2024)
This research was conducted at the Microbiology Laboratory of UIN Walisongo Semarang to identify and analyze the catalase enzyme in rhizosphere bacteria around the Laboratory of Campus 2 of UIN Walisongo Semarang. This research was carried out in several stages, namely isolation of rhizosphere bacteria, characterization of rhizosphere bacteria, gram staining of rhizosphere bacteria, and catalase test of rhizosphere bacteria. The data analysis technique used is the descriptive data analysis technique. The results showed that 9 isolates of rhizosphere bacteria produced catalase enzyme in the presence of gas bubbles when reacted with H2O2.